GEOLOGI DAN POTENSI SUMBERDAYA BATUBARA, DESA TALANG LAMBAITAMPUI, KECAMATAN SEKAYU, KABUPATEN MUSI BANYUASIN, PROPINSI SUMATRA SELATAN - Mirza Adiwarman (Hexatech: Jurnal Ilmiah Teknik, 2022)
The research area is located in Tanah Abang village, Sekayu district, Musi Banyuasin district, South Sumatra province. This research was conducted through three stages, namely the preliminary stage accompanied by data collection, the analysis and interpretation stage, and the completion and data presentation stage. Stratigraphy in the study area is divided into three rock units from old to young, namely the Muara Enim Sandstone unit, at the top the Muara Enim Claystone unit is deposited in harmony. In the study area there are two main coal seams, where both seams can be drawn continuously. The Calculation of Seam X Coal Resources Inferred Estimated Distance is 400 meters Total tonnage:1,364,626.9 tons. Calculation of Seam Y Coal Resources Inferred Distance Estimated 400 mTotal tonnage : 278,952.7 tons. Calculation of Seam X Coal Resources Indicated Distance Estimated 750 m Total tonnage : 3,016,306 tons. Calculation of Seam Y Coal Resources Indicated Estimated Distance 750 m Total tonnage : 524,890.6 tons. Calculation of Coal Resources of Seam X Measured Distance Estimated 1100 m Total tonnage : 4,775,195.4 tons Calculation of Coal Resources of Seam Y Measured Distance Estimated 1100 m Total amount of tonnage : 701,819.3 tons.